(untitled) (Advances in Civil and Architectural Engineering, 2021)
Local self-government units often consider project management as an accompanying activity and therefore do not accord it the appropriate level of importance. The term “agile” refers to a series of methods developed for more flexible project management. Thus, the background of an agile concept and its content are presented in this paper. Furthermore, the concept is compared with traditional project management methodologies. However, a priori implementation of agile-based model in an unrealistic solution can cause more damage than good. Hence, this paper proposes an agile-based matrix organizational model that adapts to the needs and particularities of the work environment in which it implemented, especially the various activities of government bodies. The model will define a new and flexible management structure for local self-government units based on the development of human resources, constant change of culture, and regular activities of government bodies, thereby improving their reliability and effectiveness.